The vulnerability of the Nothofagus forest-steppe ecotone to climate change: Palaeoecological evidence from Tierra del Fuego (∼53°S) - Mansilla Andrade, Claudia Andrea; McCulloch, Robert D.; Morello Repetto, Flavia (My University, 2018)
A new Late glacial-Holocene palaeoenvironmental record from near Lago Lynch (53 degrees 54'S, 69 degrees 26'W), Tierra del Fuego is presented. The record was sampled from a mire located within the deciduous Nothofagus forest-steppe ecotone and pollen and spore analysis suggest a high degree of vulnerability of past vegetation to changes in effective moisture. AMS radiocarbon dating supplemented by the application of tephrochronology including the geochemical fingerprinting of six visible and cryptotephra layers provides robust age constraint. The Lago Lynch record commences at c.15.6 ka. The sequence of vegetation changes between c.15.6 and 14.4 ka reflect a gradual increase in temperature and humidity followed by a colder interval between c.14.4 and 13.3 ka, which is broadly coeval with the Antarctic Cold Reversal. After c.13.3 ka patches of Nothofagus forest appeared, suggesting more mesic-temperate conditions leading gradually to the establishment of an open-canopy Nothofagus forest by c.12.5 ka which marks the start of the Holocene. Moderate to strong effective moisture levels dominated during the early Holocene until c.11.0 ka, followed by a sustained period (c.11.0-6.5 ka) of drier climatic conditions, particularly two arid phases at c.10.5-10.0 ka and 8.5-6.5 ka. An eastwards expansion of the forest margin after c.6.5 ka at the site suggests a return to more humid conditions during the late Holocene. We argue that the periods of increased moisture and aridity inferred from Lago Lynch closely reflect the extent to which the southern westerly winds (SWWs) push eastwards to the drier regions of Fuego-Patagonia during the Holocene. The longitudinal variations in moisture are driven by the nature and timing of latitudinal shifts in the SWWs. More significantly the vulnerability of the forest-steppe ecotone to moisture changes amplifies the ecological impact of relatively small-scale shifts in the SWWs.
Keywords: palynology; pollen preservation; tephrochronology; last glacial-interglacial transition; holocene; southern beech